2002
DOI: 10.1021/nl015576g
|View full text |Cite
|
Sign up to set email alerts
|

Studies into the Storage of Hydrogen in Carbon Nanofibers: Proposal of a Possible Reaction Mechanism

Abstract: Substantial levels of hydrogen, up to 6.5 wt %, have been stored in carbon nanofibers (CNFs) under conditions of 12 MPa pressure and ambient temperature. The magnitude of this result cannot be interpreted in terms of physisorption on the external surface alone. Kinetic studies indicate that a slow chemisorption process is involved. The rate of uptake corresponds to that of hydrogen dissociation on graphite edge sites. Such a finding proposes a novel mechanism, offering a plausible explanation for these unusual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(98 citation statements)
references
References 34 publications
2
93
2
Order By: Relevance
“…Oxygen functional groups have also been shown to play a role in physisorption of hydrogen on activated carbon: increasing oxidation of an activated carbon resulted in increased physisorption [12]. Graphitic carbon may be capable of dissociating hydrogen [13]; in fact, several groups have asserted that carbon nanotubes and nanofibers are capable of hydrogen dissociation and that this hydrogen in turn is able to intercalate the interlayer spacing of graphite nanofibers [14]. The effect of surface functionalities on hydrogen spillover to carbon has not been widely stud-ied, but hydrogen spillover has been shown to chemically modify functional groups on carbon to form basic carbons [15].…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen functional groups have also been shown to play a role in physisorption of hydrogen on activated carbon: increasing oxidation of an activated carbon resulted in increased physisorption [12]. Graphitic carbon may be capable of dissociating hydrogen [13]; in fact, several groups have asserted that carbon nanotubes and nanofibers are capable of hydrogen dissociation and that this hydrogen in turn is able to intercalate the interlayer spacing of graphite nanofibers [14]. The effect of surface functionalities on hydrogen spillover to carbon has not been widely stud-ied, but hydrogen spillover has been shown to chemically modify functional groups on carbon to form basic carbons [15].…”
Section: Introductionmentioning
confidence: 99%
“…Use of a Sievert's apparatus with a differential pressure transducer was reported to give reproducible hydrogen uptakes of +/-0.1% for 100 mg of sorbent. 15 In our case, use of 100 mg sample is calculated to give 0.2% error, based on both sample replicates and propagation of error.…”
Section: B Volumetric Methodsmentioning
confidence: 99%
“…Panella et al [27] reported that the hydrogen storage capacities of carbon materials are proportional to their micropore volumes. However, it has previously been reported [28,29] that specific surface areas and micropore volumes are not necessarily the primary markers for greater hydrogen storage capacity. In addition, it is possible that the investigated metals play intermedimicropores and mesopores.…”
Section: Hydrogen Storage Capacitymentioning
confidence: 97%